Analisis Bibliometrik Dampak Teknologi Digital dalam Inovasi dan Personalisasi Pembelajaran Menggunakan Vosviewer - Ina Silfina; Yoyok Soesatyo; Jun Surjanti; Retno Mustika Dewi (Universitas Pendidikan Ganesha, 2025)
This study aims to evaluate the impact of digital technology on innovation and personalization in learning through bibliometric analysis using the VOSviewer software. The methodology employed is a literature review based on a bibliometric approach, where data was obtained from Google Scholar using the Publish or Perish application and further analyzed using VOSviewer. A total of 99 relevant articles from the period 2023 to 2025 were reviewed to identify topic trends, author collaboration patterns, and the frequency of key terms in academic literature. The analysis results show that terms such as “learning,” “technology,” and “personalization” are dominant themes divided into five main clusters based on thematic proximity. Through network visualization, overlays, and density, it is evident that the topics of innovation and personalization in digital technology-based learning are increasingly becoming the focus of academic research. Additionally, this study found that the use of digital technology can enhance the learning process, making it more creative, interactive, and adaptive, supported by platforms such as Learning Management Systems (LMS), Quizizz, and AI-based chatbots. These findings contribute as an intellectual map in digital education studies and as a critical reflection on the implementation of innovative technology-based learning